(untitled) (International Journal of Engineering and Computer Science, 2015)
This Weighted Guided Image Filtering(WGIF) is which involves the smoothening technique. It involves the condition that can cocerve sharp edges. The edges are given higher weightage than other areas. This is actually an extension on filtering.. The images get fused using the weighted guided filter. For fusion the image decomposed to base layer and detail layer. Using this filter the image get fused and obtain more visual quality output.